1993
DOI: 10.1002/ar.1092360410
|View full text |Cite
|
Sign up to set email alerts
|

Development of the ventriculoarterial segment of the human embryonic heart: A morphometrics study

Abstract: In the literature, discussions continue on the question whether the distal portion of the cardiac outlet segment (ventriculoarterial portion, outflow tract of the embryonic heart) is subject to a shortening (absorption, retraction) during development. In 28 human embryos ranging from 4-42 mm crown-rump length, stereological estimates of volume fractions and surface densities were used to calculate the diameter and the length of the distal outlet segment and their changes during development. A significant incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
1997
1997

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…From that time onwards the formation of valves at the atrio-ventricular and ventriculo-arterial junctions becomes more important in avoiding backward flow of the blood when the pressures in both ventricles start to increase (Van Mierop and Bertuch, 1967;Clark et al, 1986). In the human embryo, the atrioventricular cushion tissue has been reported to grow only for a limited period (Mandarim-de-Lacerda, 1991;Wenink, 1992), whereas the distal outlet segment may become thicker, but without changing its length (Thurkow and Wenink, 1993). All these data point at a diminishing role of the atrio-ventricular canal and the distal outlet segment as temporary sphincters.…”
Section: Atrio-ventricular Canal and Distal Outlet Segmentmentioning
confidence: 99%
“…From that time onwards the formation of valves at the atrio-ventricular and ventriculo-arterial junctions becomes more important in avoiding backward flow of the blood when the pressures in both ventricles start to increase (Van Mierop and Bertuch, 1967;Clark et al, 1986). In the human embryo, the atrioventricular cushion tissue has been reported to grow only for a limited period (Mandarim-de-Lacerda, 1991;Wenink, 1992), whereas the distal outlet segment may become thicker, but without changing its length (Thurkow and Wenink, 1993). All these data point at a diminishing role of the atrio-ventricular canal and the distal outlet segment as temporary sphincters.…”
Section: Atrio-ventricular Canal and Distal Outlet Segmentmentioning
confidence: 99%
“…The intersegmental junctions, which contain endocardia1 cushion tissue, are described to have a sphincterlike function before valves have developed (Goerttler, 1955;Jaffee, 1965). The atrio-ventricular cushion tissue grows only for a limited period (Mandarim-de-Lacerda, 1991;Wenink, 1992), whereas the distal outlet segment becomes thicker without changing its length (Thurkow and Wenink, 1993). In a previous report, the growth rates of the individual cardiac segments were studied .…”
mentioning
confidence: 99%
“…2,6B), very extensive remodelling might not be necessary in this area. Moreover, the final position of the aorta has been described to be established in rather early stages (Bartelings andGittenberger-de Groot, 1988, 1989) and any significant change of the length of the distal outlet segment, in the sense of "conal absorption" (Goor et al, 1972) was not found in a recent study (Thurkow and Wenink, 1993).…”
Section: Discussionmentioning
confidence: 92%